2020
DOI: 10.1002/aenm.202002861
|View full text |Cite
|
Sign up to set email alerts
|

Operando EDXRD Study of All‐Solid‐State Lithium Batteries Coupling Thioantimonate Superionic Conductors with Metal Sulfide

Abstract: Sulfide solid‐state electrolytes have remarkable ionic conductivity and low mechanical stiffness but suffer from relatively narrow electrochemical and chemical stability with electrodes. Therefore, pairing sulfide electrolytes with the proper cathode is crucial in developing stable all‐solid‐state Li batteries (ASLBs). Herein, one type of thioantimonate ion conductor, Li6+xGexSb1−xS5I, with different compositions is systematically synthesized and studied, among these compositions, an outstanding ionic conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…
cathode materials into ASSBs could further increase the specific energy substantially. [11] However, the morphological, structural, and chemical changes during cycling are highly complex [12] and the cycling performance of ASSBs at room temperature (RT) with conversion-type cathode materials, such as S, FeS 2 , or Li 2 S, is not yet satisfactory. [13][14][15] Whereas liquid electrolyte can easily infiltrate the porous cathode composite to homogeneously contact active material particles and form a fast ion transport network, this is more difficult to achieve in ASSBs.
…”
mentioning
confidence: 99%
“…
cathode materials into ASSBs could further increase the specific energy substantially. [11] However, the morphological, structural, and chemical changes during cycling are highly complex [12] and the cycling performance of ASSBs at room temperature (RT) with conversion-type cathode materials, such as S, FeS 2 , or Li 2 S, is not yet satisfactory. [13][14][15] Whereas liquid electrolyte can easily infiltrate the porous cathode composite to homogeneously contact active material particles and form a fast ion transport network, this is more difficult to achieve in ASSBs.
…”
mentioning
confidence: 99%
“…In recent years, various SEs have been synthesized with much-improved moisture stability, e.g., As-substituted Li 4 SnS 4 , [6] Sb-doped Li 10 GeP 2 S 12 , [7] and Li 6.6 Ge 0.6 Sb 0.4 S 5 I. [8] To fully realize the high energy density of ASSLBs, thin lithium metal is preferred, but lithium dendrite growth through the SE separator and SE reduction by Li metal needs to be addressed.…”
mentioning
confidence: 99%
“…Synchrotron‐based XRD (SXRD), for example, energy‐disperse XRD (EDXRD), can provide high spatial resolution (spot size in micrometers), so that it can detect the interface products by scanning across the customized cell. [ 98 ] Furthermore, the high time resolution (data acquisition in seconds) derived from the high photon flux of SR benefits to observe instantaneous interfacial evolutions with operando setups [69b,99] . Operando SXRD was always coupled with XT to provide phase analysis and images simultaneously with the nondestructive feature, as displayed in Figure a.…”
Section: Characterizations For Electrode/sulfide Interfacesmentioning
confidence: 99%
“…Zhu and co‐workers reported using SXRD to identify each component in one operating cell (Figure 16b) and then analyzed the stability of Li 6.6 Ge 0.6 Sb 0.4 S 5 I SEs during charging and discharging. [ 99 ] Very recently, Bruce et al observed the cracking and its correlation to the growth of Li dendrites within a symmetric cell (Li/Li 6 PS 5 Cl/Li) via using combined operando SXRD and XT techniques. The SXRD mapping in one 4 × 4 Mm 2 area of the Li anode clearly indicated the location and intensity of Li dendrites that were recognized by the diffraction peak of Li (110) lattice plane (Figure 16c).…”
Section: Characterizations For Electrode/sulfide Interfacesmentioning
confidence: 99%
See 1 more Smart Citation